Axial load ratio and limit for ductility design of steel fiber-reinforced concrete composite shear walls. Issue 13 (October 2022) - Zhang, Ying; Zhang, Hongmei; Li, Xin; Lu, Xilin
Serious compression failure of reinforced concrete shear walls under high axial load ratios can be effectively prevented by adding steel fibers at the bottom, combined with an imbedded steel profile in the boundary element. However, the existing axial load ratio limit for conventional reinforced concrete shear walls is not suitable for performance-based design of such composite structural member. The seismic behavior of three composite walls with different fiber volume fractions (0–2.0%) was investigated through experimental and numerical studies under the preliminarily determined axial load ratio limit. The influence of the axial load ratio and boundary element requirements on the displacement ductility was numerically quantified. Addition of fibers assisted in mitigating the crushing of bottom concrete, improving the displacement ductility, and maintaining the bearing capacity under large deformations. Subsequently, an axial load ratio limit relax of 0.1 to 0.2 was adopted for such walls with fiber volume fraction of 1.0% to 2.0% to obtain a displacement ductility consistent with traditional walls. Finally, the axial load ratio limit and corresponding requirements on boundary elements for such walls with separate ductility demand have been recommended, which can provide guidance for performance-based design of such composite walls with flexure-controlled failure mode, however, shear-controlled walls should also be investigated in further studies.